2013
DOI: 10.4048/jbc.2013.16.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Advancement Flap as Oncoplastic Breast Conservation: Report of Seven Cases and Their Cosmetic Results

Abstract: An abdominal advancement flap (AAF) is a flap that pulls the elevated abdominal skin up and creates the shape of the inferior portion of the breast by making a neo-inframammary fold. Seven patients underwent remodeling using an AAF or a method combining an AAF with other volume displacement techniques after partial mastectomy. The excision volume ranged from 15% to 35%. AAF with only mobilization of the gland flaps was performed in two cases, with lateral mammoplasty in one case, with the round block technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…If we remove only the breast tissue, an empty space appears under the conserved skin. This can be repaired by undermining a wide area or performing volume replacement [ 16 ]. However, if we remove the over-lying skin together, volume replacement or volume displacement using a skin-glandular flap can be safely performed, with excellent results achieved [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we remove only the breast tissue, an empty space appears under the conserved skin. This can be repaired by undermining a wide area or performing volume replacement [ 16 ]. However, if we remove the over-lying skin together, volume replacement or volume displacement using a skin-glandular flap can be safely performed, with excellent results achieved [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 2 , our procedure is a modified version of the technique reported by Ogawa et al Those authors reported that the combination of the creation of a neoinframammary line and the extended mobilization of the gland flaps helped create breast volume [ 16 ]. We modified this technique not for volume creation but to maintain symmetry of the bilateral inframammary line level.…”
Section: Discussionmentioning
confidence: 99%